Produksi Biolistrik menggunakan Microbial Fuel Cell (MFC) Lactobacillus bulgaricus dengan Substrat Limbah Tempe dan Tahu - Indah Sulistiyawati; Nur Laila Rahayu; Fitria Septiana Purwitaningrum (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
The use of electricity in Indonesia with energy sources from fossils still dominates compared to other energy sources. Of the total power plant capacity in the country today, coal-fired steam power plants (PLTU) still dominate, namely 24,883 MW or 48% of the total domestic generating capacity of 52,231 MW. Fossil as a non-renewable fuel is produced continuously and will certainly run out. Development of renewable alternative energy is needed and the amount is not limited to being a renewable energy source. An alternative renewable energy source that has been developed to produce alternative electrical energy, one of which is a microbial fuel cell (MFC). This study aims to utilize Lactobacillus bulgaricus bacteria to metabolize waste water tofu and tempeh as a substrate in the MFC system to produce electrical energy. Research using tofu waste substrate has been carried out, but the use of tempe waste substrate has never been done, and the use of a mixture of waste substrate is not yet known. Microbial Fuel Cell (MFC) using L. bulgaricus in tofu waste produced a potential voltage with the highest yield of 282 mV and the number of bacterial cells reached 12.4 x 106 CFU / mL at the 5th hour incubation, whereas the mixture of tempeh and tofu waste produces a bioelectric potential of 274 mV at the 3rd hour incubation